2021
DOI: 10.1080/00472778.2021.1955122
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social responsibility in family firms: A systematic literature review

Abstract: The field of CSR in family firms has experienced remarkable growth recently. Therefore, a literature review on the topic is needed to provide an updated overview of extant research and draw guidelines for future research. Using bibliometric mapping, we conducted a systematic literature review (SLR) on corporate social responsibility (CSR) in family business drawing on the Web of Science (WOS) and Scopus databases. The bibliographic coupling conducted suggests that family involvement, corporate governance, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
76
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(86 citation statements)
references
References 189 publications
(359 reference statements)
3
76
0
7
Order By: Relevance
“…This study confirmed the great social commitment of family businesses to maintaining the welfare of society and the continuity of the company in emergencies, in line with García-Sánchez and García Sánchez [31]. Mariani et al [32] stated that FBs are more likely to invest in and be more engaged with CSR practices than non-family businesses.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This study confirmed the great social commitment of family businesses to maintaining the welfare of society and the continuity of the company in emergencies, in line with García-Sánchez and García Sánchez [31]. Mariani et al [32] stated that FBs are more likely to invest in and be more engaged with CSR practices than non-family businesses.…”
Section: Discussionsupporting
confidence: 83%
“…Due to the uncertainty generated by the pandemic, in October 2020, when the second wave caused the implementation of new restrictions, Spanish family business revenues decreased by 63% compared to the levels registered prior to the pandemic; 24% of the companies managed to maintain their sales, and 12% of the family businesses experienced an increase for various reasons, such as the adaptation of their products to the online environment, as well as adaptation to the health crisis and the new needs of the market [25]. On the other hand, a positive image of a firm regarding CSR can even lead to more sales and investments [32].…”
Section: Discussionmentioning
confidence: 99%
“…Several search criteria were deployed to retrieve the articles. First, in line with Mariani et al (2018, 2021) we developed multiple search queries entailing a combination of the focal keywords “big data” and “analytics” with the hospitality and tourism words “travel*,” “touris*,” “hospitality,” “hotel,” “leisure” in the text, abstract and keywords of the academic outputs. Second, only articles and articles in press were included (conference papers and book chapters were excluded).…”
Section: Methodsmentioning
confidence: 99%
“…According to the "Global Family Business Survey in 2020", the family firm is the most important form of enterprise in the global economy, accounting for more than 85% of firms in the world. In most countries, family firms are the backbone of the national economy [9], making significant contributions to job creation, gross national production, and wealth generation [10]. Different from nonfamily firms that perform CSR mainly to enhance corporate reputation and, hence, firm financial performance [5,6], family firms are long-term oriented [11] and perform CSR more for non-financial and socioemotional reasons, such as enhancing family image and family reputation to maintain family control and influence, achieving transgenerational succession and sustainable development [1,3], and serving the community better to gain social ties for the family firm [12,13].…”
Section: Introductionmentioning
confidence: 99%